2021
DOI: 10.1002/hed.26695
|View full text |Cite
|
Sign up to set email alerts
|

The value of 68Gallium‐DOTATATE PET/CT in sinonasal neuroendocrine tumor management: A case series

Abstract: Background 68Gallium‐DOTATATE (68Ga‐DOTATATE) is a somatostatin analog used as a PET tracer to successfully identify neuroendocrine tumors (NETs). Due to the rarity of sinonasal NETs, there are few recommendations for 68Ga‐DOTATATE imaging in these patients. Methods We discussed the impact of 68Ga‐DOTATATE imaging on the management of six sinonasal NET cases and reviewed existing literature. Results 68Ga‐DOTATATE PET/CT revealed an unknown primary in one case and identified metastatic disease in a primary sino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Despite this multimodal approach, it remains highly challenging to diagnose sinonasal tumors, and there are very few disease‐specific indicators that provide clinically meaningful information upfront, with clinicians requiring tissue analysis to guide therapy. Novel applications of imaging have been reported, such as the use of 68 Gallium‐DOTATATE for detection of ONB 2217,2218 . The WHO will likely continue to refine their tumor classification system based on new insights in molecular/genomic analytics, biomarkers, and tumor biology (e.g., SNUC as stratified into multiple diseases through DNA methylation‐based classification) 2219 .…”
Section: Research Opportunities and Future Directionsmentioning
confidence: 99%
“…Despite this multimodal approach, it remains highly challenging to diagnose sinonasal tumors, and there are very few disease‐specific indicators that provide clinically meaningful information upfront, with clinicians requiring tissue analysis to guide therapy. Novel applications of imaging have been reported, such as the use of 68 Gallium‐DOTATATE for detection of ONB 2217,2218 . The WHO will likely continue to refine their tumor classification system based on new insights in molecular/genomic analytics, biomarkers, and tumor biology (e.g., SNUC as stratified into multiple diseases through DNA methylation‐based classification) 2219 .…”
Section: Research Opportunities and Future Directionsmentioning
confidence: 99%
“…18 FDG-PET/CT can play a particularly important role in the surveillance of patients with some subtypes of rare sinonasal malignancies. For patients with high-grade SNEC, recurrence can present locoregionally or distantly metastasis, perhaps warranting closer surveillance of these patients with 18 FDG-PET/CT [49,50] . There are no definitive recommendations regarding the use of Gadolinium-DOTATATE PET/CT for SNEC, but a few reports have evaluated its utility for diagnosing low-grade SNEC where no radiotracer uptake was found on FDG PET/CT [51] .…”
Section: Pet/ctmentioning
confidence: 99%
“…A total of 3 studies were included discussing the utility of other radiotracers in the management of sinonasal malignancies (Table 8). 16,59,60 The first study compared FDG-PET to 11 C-choline PET scan and concluded that both radiotracers could help distinguish SCC from benign lesions through higher SUV values. However, when looking at all malignant tumors, FDG uptake was variable with some cases of adenocarcinoma with low uptake.…”
Section: Miscellaneous Articlesmentioning
confidence: 99%